2013
DOI: 10.1016/j.jvs.2013.07.021
|View full text |Cite
|
Sign up to set email alerts
|

A 14-year Experience with Aortic Endograft Infection: Management and Results

Abstract: Objective: We report the uptake, length of stay and vascular readmission rates of carotid endarterectomy (CEA) and CAS among patients with symptomatic or asymptomatic carotid artery disease in the English National Health Service (NHS).Methods: Retrospective cohort study based on routinely collected Hospital Episode Statistics (HES) inpatient data. We identified individual admissions for CEA (n = 15996) or CAS (n = 632) between 2006 and 2009. Summary data were used to describe procedure volumes between 2009 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 0 publications
1
31
1
8
Order By: Relevance
“…6e10 Conversely, and often despite prolonged antimicrobial treatment, mortality within 2 years can approach 100% if an infected endograft is left in situ. 6,11 The diagnosis and management of AGI is highly complex, clinical manifestations are protean, and there is no "goldstandard" diagnostic test. 3,5 In the existing literature, radiological data are mostly descriptive, microbiology details are brief or incomplete, and there have been no well designed trials of the optimum antimicrobial agent(s), route of administration, and treatment duration.…”
Section: Introductionmentioning
confidence: 99%
“…6e10 Conversely, and often despite prolonged antimicrobial treatment, mortality within 2 years can approach 100% if an infected endograft is left in situ. 6,11 The diagnosis and management of AGI is highly complex, clinical manifestations are protean, and there is no "goldstandard" diagnostic test. 3,5 In the existing literature, radiological data are mostly descriptive, microbiology details are brief or incomplete, and there have been no well designed trials of the optimum antimicrobial agent(s), route of administration, and treatment duration.…”
Section: Introductionmentioning
confidence: 99%
“…Overall mortality rates are similar to the reports of the current literature, with post-operative mortality (23.1% overall, 37.5% for iEVAR, and 0% for iOAR) after aortic graft infection. 2,9,16 The study showed that explantation of an infected conventional graft was related to significant lower 30 day mortality rates and peri-operative complications than the iEVAR group. The clinical presentation probably plays a crucial role on the outcome; of note in the series gastrointestinal bleeding was the dominant presentation in the iOAR group; however, contained rupture and abdominal pain were the dominating clinical symptoms in the iEVAR cohort.…”
Section: Discussionmentioning
confidence: 94%
“…In particular endograft (iEVAR) or conventional aortic graft infection (iOAR) represents one of the most serious complications after aortic aneurysm treatment. 1,2 Reported rates of iEVAR ranges from 0.2% to 0.7% and up to 2% for conventional grafts. 3,4 A cumulative incidence of aortic graft infection of 0.44% has been reported in population based studies.…”
Section: Introductionmentioning
confidence: 99%
“…Contact of suture line, vascular prosthesis or endovascular anchors with bowel (usually duodenum), and endograft migration or its severe angulation can lead in the longer postoperative period to the development of aorto-enteric fi stula (AEF). At the time of vascular reconstruction, almost 90% of patients have one or more factors predisposing to graft infection (5,6).…”
Section: Risk Factorsmentioning
confidence: 99%